Punishment and Shame : a Philosophical Study. - Hamblet, Wendy C. (Lexington Books, 2010)
Punishment and Shame: A Philosophical Study reveals the economic and religious underpinnings to modern notions of crime and punishment. Contra Michel Foucault's claim that modern penal practices witness a revolution in Western moral sensibilities, awakened by Enlightenment ideals, Hamblet shows that punishment practices in the West grew out of Protestant moralizations, capitalist greed, and the need for a cheap labor pool.